Toxicity and chemical transformation of silver nanoparticles in A549 lung cells: dose-rate-dependent genotoxic impact. Issue 3 (26th February 2021) - Bobyk, Laure; Tarantini, Adeline; Beal, David; Veronesi, Giulia; Kieffer, Isabelle; Motellier, Sylvie; Valsami-Jones, Eugenia; Lynch, Iseult; Jouneau, Pierre-Henri; Pernet-Gallay, Karin; Aude-Garcia, Catherine; Sauvaigo, Sylvie; et al.
Abstract : Acute exposure of A549 cells to Ag-NPs induces stronger effects on DNA integrity, ROS level, cell metabolism and cell cycle than repeated exposure. Ag-NPs dissolves in both exposure conditions and Ag ions recombine with thiolated proteins. Abstract : Silver nanoparticles (Ag-NPs) are widely used as biocides, leading to contamination of the environment and possible adverse effects on humans. Recent studies revealed that the cellular response to acute exposure to Ag-NPs differs from the response to chronic exposure, although we currently lack systematic studies comparing responses to different dosing regimens. In this study, A549 lung epithelial cells were exposed to 15 nm NM300K or 59 nm PVP-coated Ag-NPs under two different conditions. Under these two conditions, the cells received the same total sub-lethal concentration of Ag-NPs, but the dose was either administered over a 24 hour period (acute exposure) or split over four successive days (repeated exposure). These two types of Ag-NPs were chosen as PVP-coated particles were hypothesized to dissolve more slowly than NM300K particles. EXAFS measurements confirmed this hypothesis, showing more rapid oxidation of Ag 0 -NPs to Ag I in cells exposed to NM300K. The intracellular Ag content was higher in cells exposed to NM300K, and higher in cells following acute exposure than cells exposed to repeated doses. Whatever the exposure scenario, Ag I bound to thiol-containing intracellular proteins. Both exposure regimens altered cellular metabolism, caused intracellular ROS accumulation and blocked cell cycle progression. DNA damage was only observed following acute exposure, as strand breaks in cells exposed to NM300K and oxidized DNA bases in cells exposed to Ag-PVP. This damage was concomitant with decreased DNA repair activities. Together, these results show that acute exposure of A549 cells to Ag-NPs induces stronger effects on DNA integrity than repeated exposure. Nevertheless, repeated exposure to a low concentration of Ag-NPs profoundly altered the cell's metabolism and blocked cell cycle progression, confirming that both exposure regimens have detrimental effects.